The Influence of Compensation on Employee Work Motivation at PT. Matahari Department Store at Mega Trade Center Megamas Manado - Diana Wangania; Stephanus Stephanus; Rosmini Wali; Mei Hastuti; Kharies Dwi Manossoh Purnomo; Hendry Rumengan; Frangky Robial; Christian Tarandung (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Sampling was carried out using the Sevila (Slovin) formula with a precision of (5%). The sample size is 80 employees, using the survey method. Data collection was carried out by distributing questionnaires and data processing using correlation analysis and simple linear regression. The results of the t test obtained t-count = 19.447 > t-table = 0.632, then t-count = 19.447 > t-table 0.632. By comparing the t-table with the t-count, the compensation variable (X) influences employee work motivation. The results of the F test obtained F-count = 378.174 > F-table 3.951 with a significance value of 0.05, which was proven by the effect through the t test, obtained t-count = 19.447 > t-table 1.66462, so H1 was accepted and Ho was rejected. The results of this research show that compensation has a positive effect on employee work motivation at PT. Matahari Department Store at Mega Trade Center Megamas Manado.